Instrumen dan Pengumpulan Data dalam Meningkatkan Kualitas Data pada Penelitian Pendidikan - Sih Pujiharti, Endang; Isnaini, Umi (Program Studi Manajemen Pendidikan Islam (MPI) STAI Nahdlatul Ulama (STAINU) Malang, 2025)
Educational research aims to improve the quality of education and solve various problems faced in the teaching and learning process. Educational research can be carried out using a qualitative approach or a quantitative approach. Data is a very important factor in research. To obtain quality data, researchers must use valid and reliable research instruments, and follow systematic and objective data collection procedures. Testing the validity and reliability of instruments is an important step in educational research to ensure that the instrument to be used can measure what it wants to measure accurately and consistently. Selection of appropriate data collection methods according to the research objectives, type of data required, and characteristics of the research subjects. It is also important to ensure that data collection is carried out systematically, objectively and ethically to minimize errors and maximize the validity of the data.